Three-dimensional MRI-based computational fluid modeling of the left ventricle for patient before and after surgical ventricular restoration - Khalafvand, Seyed Saeid (2013)
This study was to simulate the left ventricular (LV) flow in the human heart via combination of computational fluid dynamics (CFD) and magnetic resonance imaging (MRI). MRI was performed for a heart failure (HF) patient before and 4- month after surgical ventricular restoration. The geometry included LV, left atrium (LA) and ascending aorta derived for 25 frames during one cycle from MRI data. After reconstruction of time dependent geometries and producing intermediate grids, 3D CFD modeling is performed for both before and after surgery. Intermediate geometries are generated to provide fine enough time steps for CFD modeling and discontinue time step fashion is used. The results showed that velocity of blood in LV increased after surgery and more powerful vortices exist than before surgery LV. Combined CFD/MRI for patients before and after surgery with different heart diseases could facilitate better understanding of flow pattern and research into ways to optimize and refine surgical treatment approaches in the future.